FAKTOR DEMOGRAFI PENENTU PEMILIHAN AKDR POST PLASENTA: ANALISIS UMUR DAN PARITAS - Riani, Evicenna Naftuchah; Suswanti, Osni (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2025)
Background: Postpartum contraception, particularly post-placental intrauterine device (IUD) insertion, is an effective method to delay or prevent pregnancy immediately after childbirth. Maternal factors such as age and parity are presumed to influence decision-making in the use of post-placental IUDs. This method is especially important for mothers at high risk to help regulate birth spacing and reduce maternal and neonatal mortality rates. Objective: This study aimed to analyze the influence of maternal age and parity on the use of post-placental IUDs in Banyumas Regency during 2023–2024. Methods: This research employed a retrospective cohort design involving 1,095 vaginally delivered mothers in 2023–2024. A total of 259 respondents were selected using purposive sampling. Data were obtained from delivery register books and analyzed using the Spearman rank test to determine the relationship between age, parity, and post-placental IUD use. Results: The majority of respondents were aged 20–35 years (76.8%) and were multiparous (62.2%). The bivariate analysis showed no significant effect of age (p=0.399) or parity (p=0.717) on post-placental IUD use. Conclusion: Maternal age and parity did not have a significant influence on the use of post-placental IUDs in Banyumas Regency during 2023–2024. Continuous education and counseling are recommended to improve postpartum mothers’ understanding of the benefits of long-term contraception.